STRATEGI PEMERINTAH KOTA BANJAR DALAM PENGATURAN BATAS DAERAH - Endah Vestikowati; Garis, Regi Refian; Septiana , Anggun Mustika (Journal Education and Government Wiyata, 2023)
The aim of this research is to find out the strategy of the Banjar City Government in setting regional boundaries. This study used qualitative research methods with seven informants. Data collection techniques were carried out through observation, interviews, documentation and literature study. Meanwhile, data analysis techniques were carried out through three stages, namely in the form of data reduction, data presentation, and conclusions. Based on the research results, it was concluded that the Banjar City Government's strategy in setting regional boundaries was carried out through a) Corporate Strategy; b) Program Strategy; c) Resource Support Strategy; and d) Institutional Strategy.